2010
DOI: 10.1248/bpb.33.1971
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Cardiac Size and Function in SHRSP.Z-Leprfa/IzmDmcr Rats, a New Animal Model of Metabolic Syndrome

Abstract: Lifestyle-related diseases-visceral obesity, hypertension, dyslipidemia and glucose intolerance-are known to appear in a cluster referred to as metabolic syndrome. As the number of disease components in metabolic syndrome increases in a patient, the structure and function of the heart becomes more compromised. 1) For example, metabolic syndrome increases the risk of atrial enlargement and fibrillation 2,3) and left ventricular hypertrophy and diastolic dysfunction. 1,4) These structural and functional abnormal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 39 publications
1
14
1
Order By: Relevance
“…SHRSP fatty rats exhibit major biochemical features of metabolic syndrome, in that they spontaneously develop obesity and severe hypertension, and exhibit hyperlipidemia and abnormal glucose tolerance at an early age (Hiraoka-Yamamoto et al 2004;Ueno et al 2008). We have demonstrated that impaired coronary vasodilation, ventricular hypertrophy, and diastolic dysfunction occur in SHRSP fatty rats Tada et al 2010), as shown in metabolic syndrome in humans (Guize et al 2008). SHRSP fatty rats may therefore be a useful model for evaluating the pathogenesis of cardiac dysfunction in metabolic syndrome.…”
Section: Introductionmentioning
confidence: 73%
“…SHRSP fatty rats exhibit major biochemical features of metabolic syndrome, in that they spontaneously develop obesity and severe hypertension, and exhibit hyperlipidemia and abnormal glucose tolerance at an early age (Hiraoka-Yamamoto et al 2004;Ueno et al 2008). We have demonstrated that impaired coronary vasodilation, ventricular hypertrophy, and diastolic dysfunction occur in SHRSP fatty rats Tada et al 2010), as shown in metabolic syndrome in humans (Guize et al 2008). SHRSP fatty rats may therefore be a useful model for evaluating the pathogenesis of cardiac dysfunction in metabolic syndrome.…”
Section: Introductionmentioning
confidence: 73%
“…Conversely, consumption of fructose enhances plasma triglycerides by stimulation of de novo lipogenesis in rodents and man [30] and simultaneously lowers HDL in CETP carrying species. the SHRSP fatty rats, Nile grass rats and Israeli sand rats [31][32][33]. Other animal models have been described that also possess this combination of features, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Ventricular tissue samples were removed, homogenized in lysis buffer with dithiothreitol (DTT), and centrifuged (10,000 g) for 15 min at 4°C [43]. Western blots were performed on supernatants with antibodies to phospholamban (PLB) monomers (1:5000 dilution, Abcam PLC, Cambridge, UK), phosphorylated-PLB (Ser16) (1:1000 dilution, Santa Cruz Biotechnology Inc., CA, USA), sarco/endoplasmic reticulum Ca 2 + -ATPase (SERCA) 2 (1:1000 dilution, Thermo Fisher Scientific Inc., MA, USA) and α-sarcomeric actin (Sigma-Aldrich Co., Missouri, USA, 1:20,000).…”
Section: Determination Of the Amounts Of Intracellular Ca 2+ Regulatomentioning
confidence: 99%